Pengaruh Ekonomi Terhadap Perceraian di Kabupaten Pacitan - Azis, Mansur (Institut Agama Islam Negeri Ponorogo, 2021)
Marriage is a social bond or legal agreement between individuals that forms kinship. Marriage aims to announce and give a new status to a married couple to others, so that this couple is accepted and recognized as a legal partner according to law, religion, custom and state. With the husband and wife bond, there will be continuous interaction between these two different people, this interaction can also determine harmony in the family, and disharmony in the family that can have an impact on divorce. The purpose of this study was to analyze the economic effect in terms of education, type of work and income on divorce in Pacitan district. The research method used is quantitative research methods. The sampling technique uses cluster sampling. The sample in this study was the people of the Pacitan district who divorced in 2019. Data collection techniques used questionnaires, documentation interviews and observations. The method of analysis uses descriptive statistics, classical assumption test, multiple regression analysis, t test, F test, and coefficient of determination (R2). The results of this study indicate that 1) Education has a significant effect on divorce in Pacitan Regency in 2019, 2) Type of work has no significant effect on divorce in Pacitan Regency in 2019, 3) Income has a significant effect on divorce in Pacitan Regency in 2019, 4)) Economy (Education, type of work, and income) have a significant effect on divorce in Pacitan district in 2019 with a large influence of 38.3% while the remaining 72.7% is influenced by other variables outside of this research model. Pernikahan adalah ikatan perjanjian hukum antar pribadi yang membentuk hubungan kekerabatan. Pernikahan bertujuan untuk mengumumkan dan memberikan status baru pada pasangan suami istri kepada orang lain, supaya pasangan ini diterima dan diakui statusnya sebagai pasangan yang sah menurut hukum, agama, adat, dan negara. Dengan adanya ikatan suami istri maka akan terjadi interaksi terus menerus antara dua insan yang berbeda ini, interaksi ini juga dapat menentukan keharmonisan dalam keluarga, dan ketidak harmonisan dalam keluarga yang bisa berdampak pada perceraian. Tujuan penelitian ini adalah untuk menganalisis pengaruh ekonomi yang di tinjau dari segi pendidikan, jenispekerjaan dan pendapatan terhadap perceraian di kabupaten Pacitan. Metode penelitian yang digunakan adalah metode penelitian kuantitatif. Tekhnik sampling menggunakan cluster sampling. Sampel dalam penelitian ini adalah masyarakat kabupaten pacitan yang melakukan perceraian ditahun 2019. Tekhnik pengumpulan data menggunakan angket, wawancara okumentasi dan observasi. Metode analisis menggunakan statistik deskriptif, uji asumsi klasik, analisis regresi berganda, uji t, uji F, dan koefesien determinasi (R2). Hasil penelitian ini menunjukkan bahwa 1) Pendidikan berpengaruh signifikan terhadap perceraian di kabupaten Pacitan tahun 2019, 2) Jenis pekerjaan tidak berpengaruh signifikan terhadap perceraian di kabupaten Pacitan tahun 2019, 3) pendapatan berpengaruh signifikan terhadap perceraian di kabupaten Pacitan tahun 2019, 4) ) Ekonomi (Pendidikan, Jenis Pekerjaan, dan Pendapatan) berpengaruh signifikan terhadap perceraian di kabupaten Pacitan tahun 2019 dengan besarnya pengaruh 38,3% sedangkan sisanya sebesar 72,7% dipengaruhi oleh variabel lain di luar model penelitian ini.